Liquid hydrogen fuel tanks for commercial aviation: structural sizing and stress analysis - Gomeza, Arturo; Smith, Howard (Elsevier, 2019)
LH2 fuel tanks are one of the main drivers in the development of a commercial airplane powered with hydrogen. This article discusses the implementation of liquid hydrogen fuel tanks in future commercial airplanes focusing on the sizing of the fuel tank structure and its behavior under critical loading conditions. Fuel tanks are sized according to the mission requirements and geometrical restrictions of a conventional mid-range commercial airplane. Critical loading cases for symmetrical maneuvers and landing conditions are estimated following EASA CS-25 airworthiness specifications for large airplanes. The stress distribution in each tank is evaluated using linear Finite Element Analysis (FEA) in MSC. NASTRAN/PATRAN to ensure that the structural design complies with strength and stiffness requirements
Keywords: Liquid hydrogen fuel tank; Finite element analysis; Aircraft loading; Structural sizing